2022
DOI: 10.1002/jmv.27587
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of childhood hospitalization rates and degree of severity of SARS‐CoV‐2 variants, including B.1.1.7 (Alpha), B.1.315/P.1 (Beta/Gamma), and B.1.617.2 (Delta)

Abstract: Severe acute respiratory syndrome coronavirus 2 is reappearing with an increasing number of variants every day; this study aimed to determine the effect of B.1.1.7 (Alpha), B.1.351 (Beta), P.1 (Gamma), and B.1.617.2 (Delta) variants on hospitalization rates. This single-center study was conducted at the University of Health Sciences Dr. Behçet Uz Children's Hospital from March 11 to August 27, 2021. Variant analyses of symptomatic patients admitted to the hospital who were found to be positive for COVID 19 PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Gorgels et al 26 have recently reported three large primary school outbreaks in the Netherlands, suggesting increased transmissibility of the VOC Alpha among children aged 5–12. The higher prevalence of this variant in children was also observed in studies carried out in Argentina 27 and Turkey 28 …”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Gorgels et al 26 have recently reported three large primary school outbreaks in the Netherlands, suggesting increased transmissibility of the VOC Alpha among children aged 5–12. The higher prevalence of this variant in children was also observed in studies carried out in Argentina 27 and Turkey 28 …”
Section: Discussionsupporting
confidence: 61%
“…The higher prevalence of this variant in children was also observed in studies carried out in Argentina 27 and Turkey. 28 Although RT-qPCR is considered the gold-standard method for diagnosing SARS-CoV-2 infection, pre-analytical limitations such as gRNA fragmentation due to formalin fixation can result in FFPE specimens with low viral load presenting as false negatives. 8 In this context, droplet digital PCR (ddPCR), a PCR reaction carried out individually in numerous partitions of each sample, has been demonstrated to be the most sensitive and specific test to identify SARS-CoV-2 in tissue samples.…”
Section: Discussionmentioning
confidence: 99%
“…During Alpha, Gamma and Lambda variant prevalence, the average age of children infected was higher, as was observed in a similar study in Turkey, in which mean age of children infected by new variants was reported to be 9 years. 17 During the second period of our study, a smaller proportion of cases referred to having contact with a probable or suspected COVID-19 case. Likewise, when new variants of concern appeared in other countries in Latin America, fewer children reported having been in contact with a positive case, who was not a family member.…”
Section: Discussionmentioning
confidence: 76%
“…A recent study from our center revealed that every variant reported before had different features, and the one before the Omicron variant, Delta variant (B.1.617.2), was associated with higher hospitalization rates. 1 We also compared the changing hospitalization trends of pediatric patients before and during the Omicron period in terms of age groups. Between March 2020 and January 2022, a total of 660 pediatric COVID-19 patients were reviewed retrospectively.…”
Section: To the Editorsmentioning
confidence: 99%